2020
DOI: 10.3171/2018.11.jns181338
|View full text |Cite
|
Sign up to set email alerts
|

3-Tesla MRI of deep brain stimulation patients: safety assessment of coils and pulse sequences

Abstract: OBJECTIVEPhysicians are more frequently encountering patients who are treated with deep brain stimulation (DBS), yet many MRI centers do not routinely perform MRI in this population. This warrants a safety assessment to improve DBS patients’ accessibility to MRI, thereby improving their care while simultaneously providing a new tool for neuromodulation research.METHODSA phantom simulating a patient with a DBS neuromodulation device (DBS lead model 3387 and IPG Activa PC model 37601) was constructed and used. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 18 publications
4
60
0
Order By: Relevance
“…In a previous study (15), we reported on 41 participants included in our current study. The current study expands on that study by using body transmit-receive coils and includes analyses characterizing DBS metallic artifacts seen on images from functional MRI.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study (15), we reported on 41 participants included in our current study. The current study expands on that study by using body transmit-receive coils and includes analyses characterizing DBS metallic artifacts seen on images from functional MRI.…”
Section: Methodsmentioning
confidence: 99%
“…The DBS models used are summarized in Figure 2. Participants undergoing 3-T MRI were also required to have DBS hardware geometry similar to previous phantoms (15,19,23), with redundant extension wire coiled into an extension loop (approximately 2 cm in diameter) under the scalp and the remainder of excess wire coiled behind a subclavicular IPG (Fig 3). Participants were excluded if they were unable to provide informed consent (eg, they had cognitive, psychologic, or communication impairments).…”
Section: Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advantages and pitfalls associated with the use of 3-T scanners have now been well described [10,11]. Boutet et al [12] demonstrated the safety of coils and pulse sequences of 3-T MRI of DBS patients. Voormolen et al [13] found no visible intracranial distortion in magnetization-prepared T1-weighted 7-T MRI cranial images but considerable extracranial shifts for image-guided cranial neurosurgery.…”
Section: Introductionmentioning
confidence: 99%